Infectious Arthritis - Semra Tunçbilek (Archives of Rheumatology, 2007)
Infectious arthritis is bacterial, viral, fungal, mycobacterial, or parasitic infection of single or multiple joints. The most common cause of acute bacterial arthritis is Staphylococcus aureus, and the most common risk for this is rheumatoid arthritis. Viruses cause nonsuppurative arthritis affecting multiple joints. Chronic fungal and mycobacterial arthritis are generally presents as monoarthritis and the differential diagnosis with other monoarticular arthritis is made by microbiological diagnostic methods. The main principle for the treatment of bacterial arthritis is articular drainage and antimicrobial treatment. (Rheumatism 2007; 22: 64-71)